SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF CHILDREN WITH DEVIANT BEHAVIOR - Zilola Zaripova (Modern World Education: New Age Problems – New solutions, 2026)
This article provides a scientific and theoretical analysis of the socio-psychological characteristics of children with deviant behavior. The essence of deviant behavior, its formation factors, and its impact on emotional, social, and personal development are examined. The issue of deviance is considered through sociological and psychological approaches and interpreted within the framework of Émile Durkheim’s theory of anomie, Robert K. Merton’s concept of social adaptation, and John Bowlby’s attachment theory. The study also analyzes such characteristics of children with deviant behavior as emotional instability, aggressiveness, social maladjustment, недостаточность communicative competence, and self-esteem problems. The importance of preventive measures and psychological correction is substantiated.